Implementation of Recording Earnings Management and Accounting During the Covid-19 Pandemic for Various Companies in Indonesia - Purwanti, Ari (Global Writing Academica Researching & Publishing, 2021)
The Covid-19 pandemic has caused changes in various things in the world to continue to adapt so as not to fall and be left behind. This includes the company’s ability to adapt during the pandemic, especially recording earnings management and accounting. This research will be carried out using a descriptive qualitative approach. The data earning obtained for this study comes from various previous studies that are still related to a recording of earnings management and accounting by companies during the pandemic as secondary data. The results of this study indicate that there is a vital role that accounting has in being able to reduce the negative impacts generated by the COVID-19 pandemic. Although basically accounting cannot be blamed for the adverse effects caused by the pandemic, if viewed through social science, then accounting can be considered a failure to help reduce these adverse effects.